Peningkatan Keterampilan Pedagogis dan Teknologi Guru di Era Digital Melalui Pelatihan Pengembangan Perangkat Pembelajaran Terintegrasi Etnosains Menggunakan Heyzine: (Enhancing Teachers’ Pedagogical and Technological Skills in the Digital Era through Training on the Development of Ethnoscience-Integrated Learning Devices Using Heyzine) - Dani, Rahma; Muswita, Muswita; Syaiful, Syaiful; Darmaji , Darmaji; Susanti, Nova; Hidayat, M.; Nehru , Nehru; Kurniawan, Wawan (Laboratorium Pembelajaran FKIP Universitas Jambi, 2025)
The implementation of the Merdeka Curriculum at MAN 1 Sarolangun, Jambi Province, still faces challenges, particularly in the development of learning devices that integrate local wisdom (ethnoscience) and utilize digital technology. Teachers often struggle to design innovative, contextual, and project-based learning tools, while the use of interactive digital media remains limited. In response, this community service program aims to enhance teachers’ pedagogical and technological skills through training in the development of ethnoscience-integrated learning devices using the Heyzine platform. The primary objectives of the program are to (1) improve teachers’ competence in developing Merdeka Curriculum-based learning devices integrated with ethnoscience, (2) train teachers to use Heyzine for creating interactive digital teaching materials, and (3) produce innovative, contextual, and accessible learning resources for students. Expected outcomes include the production of at least ten interactive learning devices, a comprehensive 'Local Ethnoscience Integration Map,' scientific publications, Intellectual Property Rights (IPR) registration, and dissemination through national journals and mass media.Socially and educationally, this program is expected to increase teacher creativity, student engagement, and the relevance of learning to local cultural contexts. Moreover, the integration of ethnoscience with digital platforms will strengthen the sustainability of Merdeka Curriculum implementation and contribute to educational innovation in the digital era. Abstrak. Pelaksanaan Kurikulum Merdeka di MAN 1 Sarolangun, Provinsi Jambi, masih menghadapi tantangan, terutama dalam pengembangan alat pembelajaran yang mengintegrasikan kebijaksanaan lokal (etnosains) dan memanfaatkan teknologi digital. Guru sering kesulitan merancang alat pembelajaran inovatif, kontekstual, dan berbasis proyek, sementara penggunaan media digital interaktif masih terbatas. Sebagai tanggapan, program layanan masyarakat ini bertujuan untuk meningkatkan keterampilan pedagogis dan teknologi guru melalui pelatihan dalam pengembangan alat pembelajaran yang terintegrasi dengan etnosains menggunakan platform Heyzine. Tujuan utama program ini adalah (1) meningkatkan kompetensi guru dalam mengembangkan perangkat pembelajaran berbasis Kurikulum Merdeka yang terintegrasi dengan etnosains, (2) melatih guru untuk menggunakan Heyzine dalam menciptakan materi pembelajaran digital interaktif, dan (3) menghasilkan sumber belajar inovatif, kontekstual, dan mudah diakses bagi siswa. Hasil yang diharapkan meliputi produksi setidaknya sepuluh perangkat pembelajaran interaktif, peta integrasi etnosaine lokal yang komprehensif, publikasi ilmiah, pendaftaran Hak Kekayaan Intelektual (HKI), dan penyebaran melalui jurnal nasional dan media massa. Secara sosial dan pendidikan, program ini diharapkan dapat meningkatkan kreativitas guru, keterlibatan siswa, dan relevansi pembelajaran dengan konteks budaya lokal. Selain itu, integrasi etnosains dengan platform digital akan memperkuat keberlanjutan implementasi Kurikulum Merdeka dan berkontribusi pada inovasi pendidikan di era digital.